Inspiring Creativity in Diverse Organizational Cultures: An Expatriate Integrity Dilemma. Issue 1 (March 2020) - Ogbeibu, Samuel; Senadjki, Abdelhak; Emelifeonwu, Jude; Vohra, Paramjeet Singh
Abstract: Employee creativity can bolster organizational competitiveness and survival. Although, when in host countries, expatriate top management leaders (ETML) are often challenged to constantly exhibit integrity that positively impacts the creativity of employees, despite prevalent organizational cultures' (OCs) influences. Varying influences of distinct OCs and questionable ETML integrity have also been argued to have unpredictable influences on the creativity prowess of several emerging economies like Nigeria. It is, thus, unclear from the literature how ETML and distinct OCs act to inspire employee creativity. This study investigated the relationship between ETML integrity, OC and employee creativity. A cross-sectional survey design was administered to 439 participants from 22 manufacturing organizations in Nigeria, and data analysis was executed by leveraging partial least square path modelling (SmartPLS 3). Results indicated that ETML integrity and adhocracy OC have positive associations with employee creativity. Equally, clan and market OCS reflect negative associations with employee creativity. Surprisingly, ETML integrity dampens the positive relationships between adhocracy OC and hierarchy OC, and employee creativity. Furthermore, ETML integrity reinforces the association of clan OC and market OC with employee creativity. This study offers substantive and significant contributions that can be applied to emerging economies with similar concerns and context.